Biomimicry and rehabilitation of dental tissues in geriatric population - An overview - Ekta Choudhary; Vanshika Nagar (Journal of Oral Research and Review)
As the elderly population continues to grow worldwide, dental care tailored to older adults has become increasingly important. This article examines the various clinical and systemic factors that contribute to oral health challenges in geriatric patients, particularly the elevated risk of dental caries in those with remaining natural teeth. Conditions such as diabetes and heart disease can further complicate oral health, while age-related issues such as gum recession, dry mouth, and poor dietary habits increase susceptibility to caries. Emphasis is placed on preventive care and conservative treatment strategies, including topical fluoride applications and biomimetic restorations. The classification and management of both active and arrested caries in seniors are discussed, alongside treatment options for age-related tooth wear. Endodontic care in older adults presents distinct challenges due to structural changes in the pulp and canal system, requiring careful assessment and tailored planning. Technologies like teledentistry offer promising solutions to enhance care delivery for patients with mobility or access limitations. Ultimately, a minimally invasive, personalized approach that considers both oral and systemic health is vital to maintaining function, esthetics, and quality of life in aging individuals.